IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DALAM MENGURANGI KEMISKINAN DI KOTA SIBOLGA - Rio Rinaldi Lumbantobing; Erika Revida (CV. Denasya Smart Publisher, 2025)
Poverty is a serious problem facing Indonesia, including Sibolga City, and can have widespread socio-economic impacts if not addressed appropriately. The Family Hope Program (PKH), a government policy, aims to reduce poverty through conditional social assistance focused on improving access to education, health, and the social welfare of poor families. This study aims to determine how PKH is implemented in poverty reduction in Sibolga City. This study examines the policy's dimensions and objectives, resources, implementing agent characteristics, inter-organizational communication, implementer attitudes, and the social, economic, and political environment surrounding program implementation. This study employed a qualitative descriptive method with a field study approach that included in-depth interviews, observation, and documentation. Informants were selected using purposive sampling, including PKH coordinators, facilitators, and beneficiary communities. Data analysis was conducted through data reduction, presentation, and drawing conclusions to obtain a picture of PKH program implementation at the local level and the challenges encountered. The results indicate that PKH implementation in Sibolga City has been running according to the program's objectives: helping improve the socio-economic conditions of poor families through education and health, and reducing household expenditures. The human resources involved in implementing the program are adequately qualified, having received training from the Ministry of Social Affairs, while funding comes from the state budget. Communication between implementers is effective through regular coordination meetings. Challenges encountered include beneficiary mobility and limited capacity of facilitators. Overall, the Family Hope Program (PKH) plays a significant role in poverty alleviation and improving the quality of life of the poor in Sibolga City.